2019
DOI: 10.22271/ortho.2019.v5.i2c.22
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between percutaneous cross k wire and lateral k wires fixation in management of Type III Gartland paediatric supracondylar fractures

Abstract: Introduction: Supracondylar humerus fractures are one of the commonest fractures in the paediatric age group. Displaced fractures of these kind, that is, Gartland type III are treated by closed or open reduction and k wire fixation. Cross k wire and lateral wires are the commonest configurations used for fixation. The present study aims to evaluate the difference between the two configurations in terms of surgical technique, functional outcome and complications. Materials and methods: A prospective study of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…At the final follow up, the results were analysed according to Modified Flynn's criteria. In our study, 30 out of 30 patients had satisfactory results which is comparable with Palange et al [18] study.…”
Section: Studysupporting
confidence: 91%
“…At the final follow up, the results were analysed according to Modified Flynn's criteria. In our study, 30 out of 30 patients had satisfactory results which is comparable with Palange et al [18] study.…”
Section: Studysupporting
confidence: 91%
“…Ten studies recruited only Gartland type III fractures, eight enrolled both Gartland type II and III fractures, and one included Gartland type II, III and IV fractures [ 23 ]. Six RCTs allowed the use of a third pin if required [ 23 , 25 , 28 , 29 , 34 , 36 ], while seven trials used a medial mini-open technique [ 22 , 24 , 25 , 27 , 30 , 37 , 38 ]. The follow-up widely ranged from 1.8 to 11.43 months.…”
Section: Resultsmentioning
confidence: 99%
“…Five RCTs without reporting the randomization procedure were considered to have unclear risk, and the other ten trials had low risk of such bias. Five studies reported proper allocation concealment [ 26 , 27 , 30 , 37 , 38 ]. Patients in three trials [ 26 , 27 , 30 ] and researchers assessing outcomes in six trials [ 22 , 26 , 27 , 30 , 34 , 40 ] were not blinded to interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations